EDUKASI RISIKO PENULARAN HIV DAN AIDS PADA WARGA BINAAN RUTAN KELAS IIA KOTA PALU - Arifin, Arwan; Syam, Sadli; Firmansyah; Rizki Ashari, Muhammad; Aji Satria, Muhhammad (Jurusan Farmasi FMIPA Universitas Tadulako, 2022)
HIV and AIDS are global problems and one of the public health problems in Indonesia. Prisons are places with a high risk of transmission of HIV and AIDS. The capacity of the Palu City Class IIA Prison is 180 people, with various cases. HIV and AIDS services have developed in several jails, including the jail in Palu, where imprisoned persons easily access continued care and support after receiving counselling and support. The test is a routine program in partnership with the Palu City Health Office. Prevention activities such as Information & Education Communication on HIV and AIDS and Blood Tests for Inmates in the Prison in Palu City are routinely conducted. This activity aims to increase the inmates' knowledge, attitudes, and actions to implement a healthy lifestyle and minimize the risk of transmission of HIV and AIDS, TB and other viruses. The Inmates of Class IIA Prisons in Palu City are at high risk of HIV and AIDS transmission because many crimes conducted are related to HIV transmissions, such as drug abuse with injection and sexual harassment. Moreover, some inmates have high-risk sexual behavior with other inmates, men sex with men. It is also caused by the difficulty in accessing and communicating with prisoners This community service aims to increase prisoners' knowledge, attitudes, and actions on the risk of HIV and AIDS transmission, through health education. Health education becomes a solution to changing prisoners' behavior in HIV prevention, such as stopping using a drug and safe sexual behavior.